Black Bodies, Rites in Performances and the Crossroads as a Power of Poetics of Scenes (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
From the studies in black ritual performance, considering the Congo-Angola candomblé as the centralizing philosophical axis of the research methodology of this research, it is interesting to deepen the debate on the black body in contemporaneity, in the sense of producing poetics that displace the place of the black person within the scope of the hegemonic structure that subordinates us. This xirê danced-sung-scratched-told-touched-played-expanded to the center of the circle in this conversation, aligned the place of the crossroads as a power of transdisciplinarity and the meanings of the black body in different national and international spheres.
Keywords: black ritual performance; black body; expanded Scene; negro-african traditions; ancestry